Oportunidad de los procedimientos del revisor de calidad e incidencia en auditoría - Eyzaguirre Quispe, David (2022)
Today more than ever, the audit quality control review is of fundamental importance. Such is the case that the strategy of the International Auditing and Assurance Standards Board (IAASB) for 2020-2023, and its work plan for 2020-2021, establish as one of its objectives that the International Standards constitute the basis for the development of the assignments, in a high-quality framework. In this regard, the objective of the investigation is to analyze, in detail, the activities of the quality control reviewer, in order to propose the criteria that allow determining the most opportune moments, at each stage of the audit, in which they should be applied review procedures; this is a fundamental aspect that will contribute to the quality of the assignments, so these criteria would be periodically reviewed through future research. The research is of an applied type and descriptive level, whose methodology considers as population 20 Peruvian audit firms of the 2022 ranking of the prestigious Leaders League agency, considering a non-probabilistic sample of 7 firms, in which a survey was applied, confirming the aforementioned proposed criteria, as well as their impact on the quality of the order.